A new twist on an old molecule: a rotameric isomer of bis(pentafluorophenyl)mercury. Issue 17 (26th January 2022) - Guo, Zhifang; Huo, Ryan; Tan, Yu Qing; Flosbach, Niko T.; Wang, Nicole; Leonhardt, Céline; Urbatsch, Aron; Deacon, Glen B.; Junk, Peter C.; Izgorodina, Ekaterina I.; Blair, Victoria L.
Abstract: Suspending crystals of bis(pentafluorophenyl)mercury [Hg(C6 F5 )2 ] (1a ) in a saturated n -hexane solution for a prolonged period results in transformation into the new polymorph [Hg(C6 F5 )2 ] (1 b ) monoclinic P 21 / n, a  = 11.7060(3) Å, b  = 7.8531(2) Å, c  = 13.5429(4) Å, β  = 107.247(3)°, V  = 1189.00(6) Å 3 . The C-Hg-C angle in 1 b is 177.10(11)° and the pentafluorophenyl rings are rotated 74.6(1)° to each other in comparison to 1a, the form known for 50+ years, which has a rotation angle of 58.0(2)°. Polymorph 1 b could also be obtained by crystallization from chloroform, or a CHCl3 / n -hexane (1:1) mixture at −20 °C, or by seeding with a crystal of 1 b . Theoretical calculations suggest that the barrier to rotation is low. Graphical Abstract: UF0001